Biases we live by: Anglocentrism in linguistics and cognitive sciences. (November 2019) - Levisen, Carsten
Abstract: This paper explores "Anglocentrism" as a bias in contemporary linguistics and cognitive sciences. Anglo concepts dominate international discourse on language and cognition, but the influence that this Anglocentric metalinguistic discourse has on global knowledge production, research methods, and the theoretical framing of research questions is rarely debated. Three case studies on heavily "Anglicised" discursive domains are provided: (i) "the mind" – and the Anglicisation of global discourse of human personhood; (ii) "happiness" – and the Anglicisation of the global discourse of human values; (iii) "community" – and the Anglicisation of the global discourse of human sociality. With cross-linguistic evidence from Europe (Danish), and the Pacific (Bislama), the paper denaturalises the English words mind, happiness, and community and the cognitive models they stand for, demonstrating that these words are not "neutral" nor "innocent" metalinguistic descriptors. Rather, they are quintessential Anglo constructs, and as such they provide a lens on humanity that is biased towards an Anglo interpretation of the world. Finally, the paper explores the "bias" concept. Paradoxically, the bias concept is in itself a product of the Anglosphere, as as such a part of the problem. However, due to this word's meta-discursive function, the paper argues that the bias concept can become a useful Trojan Horse, a concept through which we can fight Anglocentrism from within, and pave the way for a more adequate representation of human diversity in linguistics and cognitive sciences. Highlights: Global knowledge production is hampered by an Anglocentric bias. Anglocentric biases are discursively founded on hard-to-translate Anglo keywords. Anglo keywords dominate global academia at all levels: in hypothesis-making, theorizing, and communication of results. A decanglicization of our metalanguage is needed, if we are to make progress in linguistic, social and cognitive sciences. The bias concept can act as a Trojan Horse through which we can combat Anglocentrism from inside.